Discourse Analysis on Semantic on Wake Me Up When September Ends Song Lyric by Green Day (Scripta : English Department Journal, 2026)
Discourse analysis serves as a vital tool for examining how language constructs meaning within cultural and social contexts. Semantic is part of discourse analysis. In the realm of music, song lyrics are particularly rich in semantic content, allowing for deep exploration of themes, emotions, and societal issues. This article aims to conduct a discourse analysis of the song's lyrics, focusing on both lexical and contextual meanings. A descriptive qualitative m1ethod was employed, utilizing documentation techniques to collect data from the song's lyrics. The analysis of the lyrics from "Wake Me Up When September Ends" by Green Day has uncovered 15 contextual and lexical meanings that enhance the emotional resonance of the song. These meanings reflect both personal experiences and broader societal themes related to grief and loss. Ultimately, this analysis not only sheds light on artistic expression but also emphasizes the importance of delving beyond surface meanings in song lyrics to uncover richer emotional narratives. The implications of this study extend to broader applications in understanding and interpreting lyrical content across various musical genres.